Self-concept of Sikh people in maintaining Sikhism identity in multi-religious community - Davis Roganda Parlindungan; Syahena Manwarjit (Jurnal Sosiologi Dialektika, 2022)
Attitude intolerance to followers of different religions is always based on prejudice or negative stereotypes motivated by the belief to practice and symbolize his faith. Target can relate to individual or group adherents of a different religion, except those faced by Sikhs. Study this aim to describe draft self Sikhs in maintaining identity Sikhism in a multi-religious society in the very city of Jakarta heterogeneous, especially face attitude intolerance. This study uses qualitative method with data collection using interviews, observations, and studies related to the literature on the Sikh people. These studies found out that the Sikhs as minority in the city of Jakarta get treatment and actions intolerant in various forms like verbal ridicule, prejudice, and treatment not pleasant enough to practice and symbolize his religion. This study concludes that Sikh people continue to try to be open by viewing religious identity as a non-burdening obligation, attempting to adapt to their environment, and understanding that in order to be accepted in their environment, they must be able to open themselves as a minority, particularly regarding their religious identity, and strive for public understanding of Sikhism.